Anxiety and Academical Stress Differences Between First and Sixth Year Medical Students - Celis, Juan (2001)
OBJECTIVES: To assess the state - trait anxiety and the academic stress in first and sixth year medical students. MATERIAL AND METHODS: It was a cross - sectional analytical study. Ninety - eight Universidad San Marcos medical students, Lima (fifty three ones from the first year and forty five from the sixth year), were interviewed using the State-Trait Anxiety Inventory and Academic Stress Inventory, between June - July, 2000. RESULTS: Higher levels of state and trait anxiety in first year (State Anxiety: x = 28,68; Trait Anxiety: x = 22,70) than in sixth year medical students (SA: x = 19,09; TA: x = 18,84) were found (SA: p <0,001; TA: p = 0,033). Main academic stressful situations were "work overload", "lack of time to academic duties", and "tests" in both groups. CONCLUSIONS: Levels of anxiety were significantly higher in 1st than in 6th year medical students.